FOLKLORE OF PRYKARPATTYA AS A FACTOR OF NATIONAL-PATRIOTIC EDUCATION OF YOUNGER PUPILS - Danylyuk, Tatyana (Mountain School of Ukrainian Carpaty, 2019)
Ukrainian science, its component of folk pedagogy, in particular oral folk art, serves as a significant factor in the education of love for their native land, small homeland, which forms high patriotic feelings – love for Ukraine, an understanding of the importance not only of loving our country, but also of defending its independence, and soon. This problem is updated by the basic state documents (Law of Ukraine "Oneducation", Law of Ukraine "On extracurricular education", Concept of national-patriotic education of children and youth, Concept of artistic andaesthetic education of pupils in general educational institutions, Concept of extracurricular education and upbringing, National strategy the development of education in Ukraine until the year 2021, etc.), which emphasize that the core of the system of education of apprenticeship is the national idea, patriotism, which involves the formation of love and readiness for protection that Homeland, civicduty, interest and desire to preserve national history, culture, traditions and respect for the cultural values of other peoples. Oral folk art, as well as the entire contents of education and upbringing in elementary school, can contribute to the national-cultural revival of Ukraine. First of all, it concerns the return of those cultural values of the Carpathian region, which in the era of Soviet totalitarianism were not actively used in the educational process, they are nowabletoenrich the educational process of the elementary school with their regional flavor and become an important factor in the formation and development of nationalself-awareness of young Ukrainians. The purpose of the research is to analyze the theoretical principles of using the tools of ethnography / hutsulschynozvandia in the educational process of the modern elementary school, to describe the system of work on patriotic education of pupils of Yavorivka secondary school of the I-III centuries. Kosiv district of Ivano-Frankivsk region at lessons, extra-curricular activities, out-of-school activities aimed at creating an ethno-saturated environment.